MEMORABLE TOURIST EXPERIENCE AND ITS IMPACT ON SATISFACTION AND REVISIT INTENTION: EVIDENCE FROM KEBUMEN GEOPARK, INDONESIA - Esti Dwi Rahmawati; Rahmawati Setiyani; Ana Arum Janah; Rahmat Subagyo (RADJA PUBLIKA, 2025)
This study investigates the influence of Memorable Tourist Experience (MTE) on Tourist Satisfaction (TS) and Revisit Intention (RI) among visitors to Kebumen Geopark, Central Java, Indonesia. As a newly designated geopark integrating conservation, education, and community empowerment, Kebumen Geopark holds strong potential as a sustainable ecotourism destination. Using a quantitative associative approach, data were collected through purposive sampling of tourists who had visited the geopark at least twice, and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that MTE significantly and positively affects both TS and RI, while TS also has a direct positive effect on RI. Furthermore, TS mediates the relationship between MTE and RI, confirming its role as a key determinant of tourist loyalty. The measurement model demonstrates high validity and reliability, while the structural model indicates a good level of fit (SRMR = 0.050, NFI = 0.880). These findings suggest that enhancing tourists’ memorable experiences—through novelty, authenticity, and emotional engagement—can improve satisfaction and foster repeat visitation. The study contributes empirical evidence for sustainable tourism development and provides practical insights for destination managers to strengthen Kebumen Geopark’s branding through experience-based strategies.